Historical aspects of standard negation in Semitic - Sjörs, Ambjörn (Studies in Semitic languages and linguistics, 2018)
In Historical Aspects of Standard Negation in Semitic Ambjörn Sjörs describes the grammar of verbal negation in a wide selection of Semitic languages with an emphasis on the historical change of negative expressions.